Increased IL-17, a Pathogenic Link between Hepatosplenic Schistosomiasis and Amyotrophic Lateral Sclerosis: A Hypothesis. (23rd July 2014) - Moling, Oswald; Di Summa, Alfonsina; Capone, Loredana; Stuefer, Josef; Piccin, Andrea; Porzia, Alessandra; Capozzi, Antonella; Sorice, Maurizio; Binazzi, Raffaella; Gandini, Lathá; Rimenti, Giovanni; Mian, Peter
Abstract : The immune system protects the organism from foreign invaders and foreign substances and is involved in physiological functions that range from tissue repair to neurocognition. However, an excessive or dysregulated immune response can cause immunopathology and disease. A 39-year-old man was affected by severe hepatosplenic schistosomiasis mansoni and by amyotrophic lateral sclerosis. One question that arose was, whether there was a relation between the parasitic and the neurodegenerative disease. IL-17, a proinflammatory cytokine, is produced mainly by T helper-17 CD4 cells, a recently discovered new lineage of effector CD4 T cells. Experimental mouse models of schistosomiasis have shown that IL-17 is a key player in the immunopathology of schistosomiasis. There are also reports that suggest that IL-17 might have an important role in the pathogenesis of amyotrophic lateral sclerosis. It is hypothesized that the factors that might have led to increased IL-17 in the hepatosplenic schistosomiasis mansoni might also have contributed to the development of amyotrophic lateral sclerosis in the described patient. A multitude of environmental factors, including infections, xenobiotic substances, intestinal microbiota, and vitamin D deficiency, that are able to induce a proinflammatory immune response polarization, might favor the development of amyotrophic lateral sclerosis in predisposed individuals.